Analisis Hambatan Pelaksanaan Pembelajaran Online di SDN 065854 Medan Helvetia serta Solusinya - Harlen Simanjuntak (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
The purpose of this study is to describe the obstacles in the implementation ofonline learning at the SDN 065854 District of Medan Helvetia and their solutions.Online learning is a new way in the teaching and learning process that utilizeselectronic devices, especially the internet in the delivery of learning. Online learning,completely dependent on internet network access. This condition has a direct impact onthe world of education. Formal, informal and non-formal education institutions closeface-to-face learning and switch to online learning. The transition of learning, fromwhat was originally face-to-face to online learning created many obstacles for teachers,considering this happened suddenly without any prior preparation.